Biological Functions of Let-7e-5p in Promoting the Differentiation of MC3T3-E1 Cells - Wang, Chunli; Liu, Songcai; Li, Jiaxin; Cheng, Yunyun; Wang, Zhaoguo; Feng, Tianqi; Lu, Guanhong; Wang, Siyao; Song, Jie; Xia, Peijun; Hao, Linlin (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs let-7c and let-7f, two members of let-7 family, were involved in regulating osteoblast differentiation and have an important role in bone formation. Let-7e-5p, which was also belonged to let-7 family, presented in the differentiation of adipose-derived stem cells and mouse embryonic stem cells. However, the role of let-7e-5p in osteoblast differentiation was unclear. Thus, this study aimed to elucidate the function of let-7e-5p in osteoblast differentiation and its mechanism. Firstly, we found that the let-7e-5p mimic promoted osteoblast differentiation but not the proliferation of MC3T3-E1 cells by positively regulating the expression levels of osteogenic-associated genes (RUNX2, OCN, OPN, and OSX), the activity of ALP, and formation of mineralized nodules. Moreover, we ascertained that let-7e-5p mimic down-regulated post-transcriptional expression of SOCS1 by specifically binding to the 3'untranslated region of SOCS1 mRNA. And also, let-7e-5p induced SOCS1 down-regulation increased the protein levels of p-STAT5 and IGF-1, which were both modulated by SOCS1 molecules. Furthermore, let-7e-5p abrogated the inhibition of osteogenic differentiation mediated by SOCS1 overexpression. Therefore, these results suggested that let-7e-5p regulated differentiation of MC3T3-E1 cells though JAK2/STAT5 pathway to up-regulate IGF-1 gene expression by inhibiting SOCS1. These findings may provide new insight into the regulatory role of let-7e-5p in osteogenic differentiation and imply the existence of a novel mechanism underlying let-7e-5p-mediated osteogenic differentiation.